Analysis of Customers' Visual Comfort Perception and Mood for Cafes using Colored Glass Curtain - Prabu Wardono; Yuni Maharani (ITB Journal Publisher, LPPM ITB, 2019)
People generally prefer to work or spend leisure time under natural light rather than artificial light. Direct sunlight that enters into leisure places interrupt guests when having a meal or are enjoying the surrounding natural environment. Bamboo curtains are commonly used in Indonesia to control natural light but they do not allow people to look outside. This research was aimed at solving this problem by developing three sets of colored glass curtains